Strategi Dalam Perencanaan Dan Pengembangan Bisnis - Made Ayu Alivy Khumaira; Arin Oktavia Ramadanti; Diana Putri Damayanti; Ovia Putri Rahmadani; Rusdi Hidayat; Maharani Ikaningtyas (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This article discusses strategies in business planning and development that are crucial for a company's success. The research identifies various strategies that can be employed to tackle rapidly changing market challenges and increasing competition. Through a comprehensive approach, this article explores various planning methods that can assist companies in achieving their business objectives. The findings from this research can serve as a guide for managers and business leaders in developing effective strategies to achieve long-term growth and sustainability.